Emphasizing Philosopher Jean-Jacques Rousseau’s Paradoxical Life Educational Institution: A Case Study at Vocational High Schools in Palangka Raya, Indonesia - Munte, Alfonso (Unisia, 2024)
This paper explores the culture of leadership models, especially in the context of politics in educational institutions in Indonesia, which still use top-down leadership. A leadership model that promotes segregation and echoes domination. This model is not only found in educational institutions but also the cross-border of everyday life at the local, national, and global levels. The lives of students from three vocational high schools in Buntok, Central Kalimantan, regarding their lives and naturalist intelligence across disciplinary boundaries, as well as their responses to the leadership model they received at school. Then, processed using Jean-Jaques Rousseau's philosophy of the social contract in the landscape of a democratic state, social praxis related to leadership, especially in educational institutions. This writing uses a qualitative method, in-depth interview methods, transcribing factual solids, and then making them into themes for subjects or students from 3 SMKNs in Buntok, Palangka Raya, Central Kalimantan. This research revealed that the shared leadership model is an essential contribution to the practice of learning life praxis in the context of independence learning.